The Influence of Perceived Product Quality and Service Quality on Repeat Customers Use of Japanese Restaurants - Nurittamont, Wasutida (NEU ACADEMIC AND RESEARCH JOURNAL, 2021)
The purposes of this research were 1) to study the reception of product quality, service quality on repeat customers use at Sushi Japanese Restaurant and 2) to explore the influence of product quality and service quality on repeat customers use at Sushi Japanese Restaurant. The questionnaire was used as a tool to collect data from 400 customers in Sushi Japanese Restaurant at Phra Nakhon Sri Ayutthaya Province. Moreover, a purposive sample strategy in a form of non-probability sampling was chosen to select the population in the study. The descriptive statistics and inferential statistics used to analyze test hypotheses. The result shown that the product quality and service quality on repeat customers use at Sushi Japanese Restaurant was at high level. Similarly, the factors were significantly on repeat customers use at Sushi Japanese restaurant at 0.01. Therefore, these results were as a guide line for Japanese restaurant entrepreneurs on giving service and as a guide to develop products quality and service quality to meet consumers’ need. Besides that, the result of the study was to increase capabilities to compete in the market of Sushi Japanese restaurant.